ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL MATEMATIKA PERBANDINGAN BERDASARKAN KEMAMPUAN NUMERIK - Salsabila, Adelia Nafita; ., Masrurotullaily (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
In this era of the 4.0 revolution, society is expected to be able to think creatively, namely generating new ideas to solve various problems in daily life and preparing for the future. Enhancing creative thinking ability is considered one of the main learning objectives that is important to be improved in mathematics education. To think creatively in mathematics, students need to understand and actively engage in calculation processes as well as solve problems related to numbers and symbols, which is associated with numerical ability. The objectives of this study are: 1) To describe students' creative thinking abilities in solving mathematical problems based on high numerical ability 2) To describe students' creative thinking abilities in solving mathematical problems based on moderate numerical ability 3) To describe students' creative thinking abilities in solving mathematical problems based on low numerical ability. This research is a qualitative descriptive study. The data collection techniques include tests, interviews, and documentation. The research subjects were students of class VII B at SMP Negeri 1 Tamanan, with six students selected as subjects: two with high, two with moderate, and two with low numerical ability. The results of the study showed that students with high numerical ability met the indicators of fluency and flexibility, students with moderate numerical ability met the fluency indicator, and students with low numerical ability did not meet the indicators of creative thinking ability.